CONTRIBUTION OF EXPLOSIVE POWER OF ARM MUSCLES AND FLEXIBILITY TO SMASH ABILITY OF PB. SEMEN PADANG ATHLETES - Novel Yulanda; Endang Sepdanius (JURNAL STAMINA, 2019)
The research problem was the low smash ability of SSB PSP Bangko Players. This research is a correlational study which aims to determine how much the contribution between explosive power of arm muscle and flexibility to smash of SSB PSP Bangko Players. This research is included in the type of correlational research. The population in this study were all badminton athletes who practiced in PB. Semen Padang totaling 60 people. Sampling in this study was carried out by purposive sampling technique. So, the sample in this study amounted to 20 people, namely at the main level amounting to 20 people. Data were collected using measurements on all three variables. Variables Smash ability was measured by test Smash ability, variable Explosive strength of arm muscles was measured by two hand medicine ball put tests and the Determination variable was measured by the Shit and reach test. Data were analyzed using product moment. The results of the data analysis were obtained: (1) From the results of the obtained explosive power of arm muscle contributed significantly to smash ability of SSB PSP Bangko Players, marked by the results obtained by tcount = 2.79> t table = 1.734 and give a contribution of 30%. (2) From the results obtained by flexibility, it contributes significantly to smash ability of SSB PSP Bangko Players, marked by the results obtained by t = 2.72> t table = 1.734 and contributed 29%. (3) There is a significant contribution together between arm muscle explosive power and flexibility to smash ability of SSB PSP Bangko Players, marked by the results obtained by Fcount = 10.32 > Ftable = 3.59 and contributed 55%.